Who Controls the Immigration Bureaucracy? The Relative Influence of the Three Branches Over Asylum Policy Implementation. Issue 2 (March 2023) - Stobb, Maureen; Miller, Banks; Kennedy, Joshua
At the center of contentious debates concerning U.S. asylum policy are immigration judges, bureaucrats who decide life and death cases on a daily basis. Congress, the executive and the courts compete for influence over these key actors — administrative judges distinct from those examined in much of the bureaucratic control literature. They are hired, fired, promoted or demoted by executive officials; face congressional oversight; and must follow circuit law. We argue that, because of the fear of reversal, immigration judges will look most to the courts in the decision-making process. Our results support our theory. Examining over 900, 000 immigration judges' decisions, we find that, although IJs are influenced by a fear of pushback from the elected branches, the impact is conditional on circuit preferences. Our findings inform scholarly understanding of judicial behavior and bureaucratic accountability, and support the pursuit of judicial independence and due process in immigration courts.